ID: 139: PROGRESSIVE GLOMERULAR DAMAGE IN SICKLE CELL TRAIT AND SICKLE CELL ANEMIA MOUSE MODELS. Issue 4 (22nd March 2016) - Saraf, SL; Sysol, JR; Arruda, JA; Machado, RF; Gordeuk, VR; Susma, A; Setty, S; Gudehithlu, KP; Singh, AK
Abstract : The hemoglobin S mutation, a glutamic acid to valine substitution in the β-globin chain, results in hemoglobin polymerization under hypoxic conditions and leads to vaso-occlusion and hemolysis. Homozygous inheritance (Hb SS; sickle cell anemia) affects 1 in 500 African Americans and is consistently associated with an increased risk for kidney disease which may be due to cell-free hemoglobin toxicity, ischemic injury, or hyperfiltration-mediated damage to the kidney. Heterozygous inheritance (Hb AS; sickle cell trait) affects 1 in 8 African Americans and has also been associated with an increased risk for kidney disease, although not in all cohorts and the mechanisms are not well understood. We investigated whether inheritance of the Hb S mutation resulted in incremental kidney damage in Hb AS and Hb SS mice compared to Hb AA mice by histology, proteinuria, and candidate gene expression using transgenic sickle mice ≥6 months of age (Townes model, Jackson Laboratory). Values are presented as mean±standard error and analyses are adjusted for age. Using Masson trichrome stained sections of the kidney, progressive patterns of mesangial expansion were observed in age-matched Hb AS and Hb SS mice versus Hb AA mice by renal pathologists blinded to the hemoglobin genotype (figure 1). Hb AS mice had diffuse (>50% of the glomeruli per slide being involved) mesangial expansion while Hb SS mice had diffuse and global (>50% of the individual glomerulus being involved) mesangial expansion. Glomerular perimeters were measured using NanoZoomer Whole Slide Imaging in 26 randomly selected glomeruli from 2 age-matched mice per genotype. Using the upper quartile as the definition for an enlarged glomerulus, the proportion of enlarged glomeruli progressively increased from Hb AA (15%) to Hb AS (31%) to Hb SS mice (58%) (Cochran's test of linear trend, P =0.001) (figure 2). Progressively higher kidney weights were also observed from Hb AA (429±28 mg, n=8) to Hb AS (446±27 mg, n=18) to Hb SS (567±19 mg, n=5) mice (Test for linear trend, P =0.047). We then measured urine protein and urine creatinine concentrations using the Bio-Rad dye method and Jaffé reaction, respectively. Progressively higher urine protein-to-creatinine ratios were observed from Hb AA to Hb AS to Hb SS mice (figure 3) (Test for linear trend, P =0.09). Gene expression of candidate genes ( TGFB1, IL6, MMP9, Klotho, HMOX1, and SHROOM3) was determined by rt-PCR from kidneys of age-matched, female Hb AA and Hb AS mice (n=5). Increased expression of Klotho ( P =0.09) was observed in Hb AS mice (figure 4). Klotho is a β-glucoronidase that is highly expressed in the kidney and acts as a cofactor that increases the affinity of the FGF23 ligand for the FGF receptor. In conclusion, we observed progressive glomerular injury, determined by mesangial expansion, proportion of enlarged glomeruli, and urine protein concentrations in Hb AS and Hb SS mice compared to Hb AA mice. Klotho was upregulated in Hb AS mice and may play a role in the pathophysiology of kidney damage in Hb AS which will require further investigationAbstract ID: 139 Figure 1 .